2010
DOI: 10.1348/135910710x494583
|View full text |Cite
|
Sign up to set email alerts
|

What men really want: A qualitative investigation of men's health needs from the Halton and St Helens Primary Care Trust men's health promotion project

Abstract: These results have practical implications for the way in which health promotion interventions target men, which we discuss in conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 55 publications
(75 reference statements)
7
76
0
Order By: Relevance
“…I got somebody in, it was on men specific cancers, and this lady came and gave a PowerPoint presentation. Evidence here supports previous work that recognises how the structural embedding of health as a 'feminised' concept (Robertson, 2007: 139) can create problems in addressing 'health' directly within health promotion initiatives for men (Coles et al 2010). Recognising this, listening to the men's views, their motivations for attending, and adjusting projects accordingly, was clearly key to building trust, sustaining engagement and thereby facilitating change.…”
Section: Developing and Sustaining Trustsupporting
confidence: 81%
“…I got somebody in, it was on men specific cancers, and this lady came and gave a PowerPoint presentation. Evidence here supports previous work that recognises how the structural embedding of health as a 'feminised' concept (Robertson, 2007: 139) can create problems in addressing 'health' directly within health promotion initiatives for men (Coles et al 2010). Recognising this, listening to the men's views, their motivations for attending, and adjusting projects accordingly, was clearly key to building trust, sustaining engagement and thereby facilitating change.…”
Section: Developing and Sustaining Trustsupporting
confidence: 81%
“…Shortcomings in the resources and supports available to service providers are also noted in the literature as barriers to providing meaningful and effective services for men (Carroll et al, 2014;Coles et al, 2010;Heenan, 2004;Kirwan et al, 2013;Monaem et al, 2007;L. M. Robertson, Douglas, Ludbrook, Reid, & Van Teijingen, 2008;S.…”
Section: Research-article2015mentioning
confidence: 99%
“…Findings also identify that health professionals typically used a direct approach when discussing obesity and exercise with men and a more cautious approach with women. The adoption of such an approach with men is contrary to the findings of Michie (2007) and Coles et al (2010), who highlight how feelings of stress, embarrassment and fear, during consultation may result in low male attendance at health clinics. Both of the approaches (direct and cautious) used by the health professionals in this study were based on their gender-specific views of their patients.…”
Section: Resultsmentioning
confidence: 72%
“…The notion that GPs can hold preconceived views about male behaviours has also been highlighted by Hale et al (2010), who found that GPs thought that male stoical behaviour may prevent men seeking help with chronic medical conditions. However, such views have been challenged by Coles et al (2010), who found that men generally wanted to access medical services but were inhibited due to a lack of experience at accessing those services.…”
Section: Causal Condition -Health Professionals' Viewsmentioning
confidence: 99%
See 1 more Smart Citation